SISTEM INFORMASI PENGELOLAAN PRODUKSI KAIN TENUN DI BUTIK TENUN JEPARA - Ahmad Lutfi Hakim; Arief Susanto; Aditya Akbar Riadi (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to develop an information system for managing the production of woven fabrics at Butik Tenun Jepara. This system is designed to enhance operational efficiency and facilitate data storage by transitioning from manual to digital record-keeping. The system was developed using the waterfall method, starting from requirements analysis, design, implementation, and testing. The implementation results show that this information system successfully improves the efficiency of production data and raw material stock management, minimizes recording errors, and accelerates the production process. The system also features basic authentication to differentiate between admin and employee access, ensuring data security and privacy.